INTERNATIONAL PRACTICE OF DEPOSIT POLICY DEVELOPMENT AND IMPLEMENTATION IN COMMERCIAL BANKS (Analysis of International Sciences, 2024)
The current state of the deposit policy of commercial banks of our country was analyzed in this article. During the analysis the peculiarities of systemic development of factors influencing on the process of deposit policy implementation were investigated. Also the conditions and opportunities of using of information systems and other directions of international best practice for improving the deposit policy of commercial banks were assessed. Based on the total conclusions on the organization of the system of targeted using of instruments for the development of deposit policy of commercial banks, scientific proposals and practical recommendations were developed to increase the level of capitalization and deposit base of commercial banks, to direct the strategy and tactics of deposit activity of commercial banks to strengthen their financial stability and reliability.